Meristem fate: to terminate, or not? - Lin, Chan-Yi Ivy; Irish, Vivian F. (Frontiers in Plant Science, 2026)
Plants exhibit remarkable physiological and developmental flexibility, enabling continued organogenesis, adaptation to environmental stimuli, and underpinning a vast diversity of shoot architectures. Central to this capacity is the plasticity of plant meristems, that function as dynamic sources of stem cells and define pivotal decision points between indeterminate (sustained) and determinate (finite) growth. Understanding the regulatory networks governing meristem fate is critical for both basic plant science and practical applications in crop architecture and yield optimization. In this review, we focus on the interplay between transcriptional regulators and phytohormone gradients that govern the switch between indeterminacy and determinacy in developing shoot meristems. We explore how regulatory networks converge to produce determinate structures such as flowers and thorns in different angiosperm species.